2022
DOI: 10.1371/journal.pone.0263842
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the implementation effect of public participation in the decision-making of NIMBY facilities

Abstract: The construction of NIMBY (Not in my backyard) facilities has caused many conflicts but is struggling to reduce it in China. With the background of public participation in social governance in the future, effective public participation is extremely helpful to solve this issue. Promoting public participation and scientifically evaluating the implementation effect of public participation are urgent problems to be solved at present. This study aims to analysis the factors hindering public participation and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Adaman et al (2011) also found that there is a positive correlation between institutional trust and public environmental protection behavior. Faced with social problems alone, the public is more likely to seek help from the government and various organizations (Zhao et al 2022). When the public believes that the government is inclined to protect individual environmental rights, they believe that the court holds the same behavioral preference and are more willing to take environmental litigation actions.…”
Section: Public Trust In Government Environmental Protectionmentioning
confidence: 99%
“…Adaman et al (2011) also found that there is a positive correlation between institutional trust and public environmental protection behavior. Faced with social problems alone, the public is more likely to seek help from the government and various organizations (Zhao et al 2022). When the public believes that the government is inclined to protect individual environmental rights, they believe that the court holds the same behavioral preference and are more willing to take environmental litigation actions.…”
Section: Public Trust In Government Environmental Protectionmentioning
confidence: 99%
“…Relevant studies have also analysed the current status and importance of public participation. Public participation is essential to solving NIMBY conflicts (Zhao et al 2022). Public participation and trust in administrative decision-making are crucial for getting beyond NIMBY opposition to foster public support and achieve successful siting agreements (Krause et al 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…), but also those that create a sense of unhappiness, such as funeral homes, drug rehabilitation centers, prisons, etc. [9,37]. At the same time, risk-gathering NIMBY facilities are characterized by having a high risk, large scale, and being small in number, which have an obvious industrial nature.…”
Section: Nimby Facilitiesmentioning
confidence: 99%